Herpes‐like skin lesion after AstraZeneca vaccination for COVID‐19: A case report - Mohammadreza Ardalan; Hamidreza Moslemi; Shervin Shafiei; Reza Tabrizi; Mohammadreza Moselmi (Clinical Case Reports, 2021)
Abstract Recurrent herpes simplex virus or varicella zoster virus infection should be considered as one of the rare complications after AstraZeneca vaccination for COVID‐19.